Modern German fairy stories - Trunk, Matilda (My University, 1908)
Introduction: The following stories are translations from “New German Fairy Stories” (Neuer Deutscher Marchenschatz, Sonderheft der “Woche”). August Scherl. Berlin 1905.
Citation: Trunk, Matilda. Modern German fairy stories. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Fairy Tales; German Literature; Translations; Graduating theses; Senior theses; Theses